Embodied engagement with gender and agrobiodiversity: Leveraging transformative moments in multidisciplinary teams - Elmhirst, Rebecca; Resurrección, Bernadette P.; Elias, Marlène (Routledge, 2020)
What happens when a leading international research centre that provides technical knowledge on agricultural and forest biodiversity to strengthen food security and ecosystem health is required to bring a gender perspective into its work? As part of a strategic initiative, Gender Specialist Marlène Elias was hired to take on this mantle in Bioversity International, one of the 15 CGIAR research centres (formerly the Consultative Group on International Agricultural Research). Bioversity International (hereafter, BI) was initially established as the International Board for Plant Genetic Resources and subsequently operated under the name of International Plant Genetic Resources Institute. Its early work focused on the emergency conservation of crop genetic resources in gene banks. The organisation’s focus has changed over time, and at the time of our discussion with Marlène, BI’s mission was to deliver scientific evidence, management practices and policy options to use and safeguard agricultural and forest biodiversity to attain sustainable global food and nutrition security. Since 2020, BI is in a formal alliance with CIAT (the Center for Tropical Agriculture), another CGIAR centre. The alliance of Bioversity International and CIAT aims to ‘deliver research-based solutions that harness agricultural biodiversity and sustainably transform food systems to improve people’s lives’. Bioversity International is one of the CGIAR centres contributing to the CGIAR Research Program on Forests, Trees and Agroforestry (FTA), which is the world’s largest research for development program to enhance the role of forests, trees and agroforestry in sustainable development and food security, and to address climate change. Within her remit as Gender Specialist in the realm of Conservation and Management of Forest Genetic Resources, Marlène’s work has involved implementing FTA’s cross-centre Gender Strategy, launched in 2013, and more generally, integrating gender into BI’s activities.